Characteristics and Shifts in Meaning of Affixed Words in Short Messages on WhatsApp - Ali, Ali; Firgyawan, Zyad; Tahir, Moh; Krida, Syamsuddin; Palliwi, Effendi Dg. (Journal of Authentic Research, 2022)
The use of language or words when chatting on the WhatsApp application tends to use new terms or abbreviations, thus obscuring the characteristics of words and shifting the meaning of words. This study aims to describe the characteristics and shifting meanings of affixed words in short messages on WhatsApp. The method used in this study is a qualitative descriptive method. Based on the results of the research carried out, 22 affixed words and 22 random conversations were found, including affixed words that occurred in short messages on WhatsApp. The results of the study show that the interference of using affixed words in WhatsApp short messages is a shifting of the meaning of a word or having a new meaning. The words that underwent a shift in meaning experienced expansion (generalization), narrowing (specialization), deterioration (pejoration), improvement (amelioration), exchange of meaning (synesthesia), and meaning equivalence (association). To use words well, correctly, and correctly, we need to pay attention to affixes and word classes that have a role in forming a sentence. This results in a shift in the meaning of affixed words in the affixation of the basic form or also the process of forming words by affixing, adding, or attaching affixes in front of the basic form. The results of this study can be used as an additional reference and knowledge to be more accurate in using words and sentences without losing the meaning contained in it.